2012
DOI: 10.1097/bpo.0b013e318270468b
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Intramedullary Flexible Nailing of Open Pediatric Tibial Shaft Fractures

Abstract: Level III, therapeutic study, retrospective cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 25 publications
3
55
0
1
Order By: Relevance
“…The authors believed this was largely due to the expedient administration of antibiotics in these patients within 6 hours of the injury, and meticulous soft tissue handling. 18 The advantage of flexible nails is that they are inserted at a position distinct from the traumatic wound, impart minimal damage to the surrounding soft tissue, and do not provide an infectious nidus from pin tracts. In comparison, Bartlett et al 28 found that 6 patients required free muscle flaps.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The authors believed this was largely due to the expedient administration of antibiotics in these patients within 6 hours of the injury, and meticulous soft tissue handling. 18 The advantage of flexible nails is that they are inserted at a position distinct from the traumatic wound, impart minimal damage to the surrounding soft tissue, and do not provide an infectious nidus from pin tracts. In comparison, Bartlett et al 28 found that 6 patients required free muscle flaps.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study of 14 open tibia fractures that underwent immediate flexible nailing and a control group of 12 closed tibia fractures, there was no significant difference in regards to the rate of infectious/wound complications. 18 Furthermore, all patients except 1 in this series underwent primary wound closure. With prompt antibiotic administration and meticulous soft tissue management, primary wound closure can often be performed.…”
Section: Flexible Nail Fixationmentioning
confidence: 99%
See 2 more Smart Citations
“…Für offene Frakturen wird in der Regel der Fixateur externe empfohlen, es ist aber durchaus auch eine Stabilisierung mit ESIN möglich [9], Platten werden nicht empfohlen.…”
Section: Unterschenkelunclassified